2019
DOI: 10.1093/ons/opz202
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Localization of Language Cortex in an Awake 4-Year-Old Child with Rasmussen Encephalitis: A Case Report

Abstract: BACKGROUND AND IMPORTANCE Presurgical mapping of eloquent cortex in young patients undergoing neurosurgery is critical for timely intervention, surgical planning, and minimizing postoperative deficits. However, invasive direct cortical stimulation has limited success in young children and noninvasive modalities, such as magnetoencephalography and functional MRI, require sedation, often precluding localization of critical language cortices. Transcranial magnetic stimulation (TMS), a noninvasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The color-naming task was used in eight children (see Figure 1B for example) and an object-naming task was used in five children. We have previously shown that young and developmentally delayed children who could not consistently name objects could still name colors accurately and have successfully used the color-naming task to successfully map speech and language in this cohort (32,45). In other children, pictures of objects included in the NexSpeech module was used (46).…”
Section: Language Mappingmentioning
confidence: 97%
See 1 more Smart Citation
“…The color-naming task was used in eight children (see Figure 1B for example) and an object-naming task was used in five children. We have previously shown that young and developmentally delayed children who could not consistently name objects could still name colors accurately and have successfully used the color-naming task to successfully map speech and language in this cohort (32,45). In other children, pictures of objects included in the NexSpeech module was used (46).…”
Section: Language Mappingmentioning
confidence: 97%
“…We have previously reported a small case-series of six children under the age of 3 years who underwent TMS motor mapping at our institution ( 20 ) and on the utility of TMS motor mapping in an infant with cortical dysplasia ( 31 ). We have also reported a case study of a 4-year 11-month-old child who underwent successful TMS language mapping ( 32 ). In this paper we aim to further assess whether reliable motor maps can be derived in very young children with neurological disorders and evaluate the safety and tolerability of TMS in a larger cohort of children younger than 3 years.…”
Section: Introductionmentioning
confidence: 99%